Answer :

The above given equation can also be written as,


23x = ((2)3)2x + 1 23 = 8


As we know by the laws of exponent, that,


(am)n = amn


23x = 23(2x + 1)


As the bases are same so the exponents can be equated,


3x = 3(2x + 1)


x = 2x + 1


x = -1


Value of x =-1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Express the produNCERT - Mathematics Exemplar

Simplify:

NCERT - Mathematics Exemplar

Out of the four oNCERT - Mathematics Exemplar

Out of the four oNCERT - Mathematics Exemplar

Express 16–2NCERT - Mathematics Exemplar

Express as a poweNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar